Method for testing coulombic efficiency of secondary battery electrolyte under practical condition

By injecting the electrolyte to be tested into the lithium copper soft-coated battery cell and performing charging and discharging tests, the reliability and accuracy of the Coulomb efficiency test in the existing technology is solved, and a more accurate and consistent Coulomb efficiency test results are achieved. .

CN119395545APending Publication Date: 2025-02-07EVE ENERGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411508073.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-25
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

In the prior art, the reliability of the Coulomb efficiency test is poor and the accuracy of the results is poor, so it is impossible to obtain the true Coulomb efficiency of the electrolyte under practical conditions.

Method used

Provide a method for testing efficiency of the secondary battery electrolyte under practical conditions. By preparing a lithium copper soft-coated battery cell without the electrolyte, injecting the electrolyte to be tested, forming the battery cell to be tested, and performing charging and discharging tests to obtain Coulomb efficiency.

Benefits of technology

It improves the accuracy of the Coulomb efficiency test results, avoids deviations caused by excessive electrolyte in traditional buckle battery tests, enhances the consistency of the test data, and provides a standardized way to test the electrolyte Coulomb efficiency test.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119395545A_ABST
    Figure CN119395545A_ABST
Patent Text Reader

Abstract

The invention provides a method for testing the coulombic efficiency of a secondary battery electrolyte under a practical condition, which comprises the following steps: preparing a battery cell, injecting the electrolyte and testing the coulombic efficiency, and the battery cell is a lithium-copper soft package dry battery cell without injecting the electrolyte; injecting a to-be-tested electrolyte into the lithium-copper soft package dry battery cell to form a to-be-tested battery cell; and carrying out charging and discharging test on the to-be-tested battery cell to obtain coulombic efficiency. The problems that in the prior art, coulombic efficiency testing is poor in reliability and result accuracy, and the real coulombic efficiency of the electrolyte under the practical condition cannot be obtained are solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of battery coulombic efficiency testing, and in particular to a method for testing the coulombic efficiency of a secondary battery electrolyte under practical conditions. Background Art

[0002] As a quantitative indicator of battery reversibility, coulombic efficiency has been widely used in battery research. Among them, the coulombic efficiency of lithium-copper batteries is a method to evaluate the stability of different electrolytes to metallic lithium and the lithium consumption of electrolyte side reactions during the cycle. It is a common electrolyte characterization method in lithium metal secondary batteries. At present, the lithium-copper coulombic efficiency is tested by lithium-copper button batteries. However, due to the characteristics of the button battery structure itself, the electrolyte is usually excessive during the test, and the battery pressure is uncontrollable, which cannot fully reflect the reaction between the electrolyte and the lithium negative electrode under practical conditions (such as the actual use of soft-pack batteries); and some components in the electrolyte may react with the button battery structure to cause experimental data deviation; in addition, lithium-copper button batteries are generally assembled by testers personally, and there are situations such as the inability to fix the position of the pole piece, resulting in poor consistency of the test data, and the coulombic efficiency data obtained by different test operators are not uniformly comparable. Summary of the invention

[0003] The main purpose of the present application is to provide a method for testing the coulombic efficiency of secondary battery electrolyte under practical conditions, so as to solve the problems of poor reliability, poor result accuracy and inability to obtain the true coulombic efficiency of the electrolyte under practical conditions in the prior art.

[0004] In order to achieve the above-mentioned purpose, according to one aspect of the present application, a method for testing the coulombic efficiency of a secondary battery electrolyte under practical conditions is provided, comprising preparing a battery cell, wherein the battery cell is a lithium-copper soft-pack dry battery cell that has not been injected with an electrolyte; injecting an electrolyte to be tested, injecting the electrolyte to be tested into the lithium-copper soft-pack dry battery cell to form a battery cell to be tested; and conducting a coulombic efficiency test, wherein the battery cell to be tested is subjected to a charge and discharge test to obtain the coulombic efficiency.

[0005] Furthermore, the method for testing the coulombic efficiency of secondary battery electrolyte under practical conditions also includes: when preparing a battery cell, cutting a plurality of pole pieces of a predetermined size; stacking the lithium electrode pole piece as the negative electrode, the separator and the copper electrode pole piece as the positive electrode in sequence to assemble into a lithium-copper soft-package dry battery cell; connecting the lithium electrode pole piece as the negative electrode and the copper electrode pole piece as the positive electrode to the pole ears respectively; and encapsulating the lithium-copper soft-package dry battery cell.

[0006] Furthermore, the method for testing the coulombic efficiency of the electrolyte of a secondary battery under practical conditions also includes: when cutting the pole pieces, the size of the lithium electrode pole piece as the negative electrode is smaller than the size of the copper electrode pole piece as the positive electrode.

[0007] Furthermore, the method for testing the coulombic efficiency of secondary battery electrolyte under practical conditions also includes: when the pole pieces are stacked and assembled into a dry battery cell, a separator is provided between two adjacent stacked pole pieces, and the number of lithium electrode pole pieces serving as negative electrodes is less than the number of copper electrode pole pieces serving as positive electrodes.

[0008] Furthermore, the coulombic efficiency test method of secondary battery electrolyte under practical conditions also includes: when cutting the pole pieces, the width of the lithium electrode pole piece as the negative electrode is: 55-65cm, length: 65-75cm, thickness: 30-300μm; the width of the copper electrode pole piece as the positive electrode is: 67-77cm, length: 57-67cm, thickness: 10-50μm.

[0009] Furthermore, the method for testing the coulombic efficiency of a secondary battery electrolyte under practical conditions also includes: when injecting the electrolyte, cutting the packaging film on the outside of the lithium-copper soft-package dry cell, injecting the electrolyte to be tested into the lithium-copper soft-package dry cell, and sealing the cut portion of the packaging film.

[0010] Furthermore, the method for testing the coulombic efficiency of a secondary battery electrolyte under practical conditions also includes: when preparing a battery cell, preparing a plurality of lithium-copper soft-pack dry battery cells; when injecting the electrolyte, injecting different electrolytes to be tested into different lithium-copper soft-pack dry battery cells; during the coulombic efficiency test, performing constant current charge and discharge tests on the battery cells to be tested containing different electrolytes to be tested, obtaining the coulombic efficiency of each battery cell to be tested, and comparing the coulombic efficiency of each battery cell to be tested.

[0011] Furthermore, the method for testing the coulombic efficiency of a secondary battery electrolyte under practical conditions also includes: during the coulombic efficiency test, the test environment of each battery cell to be tested is the same, wherein the test voltage range is -0.5V to 1V.

[0012] Furthermore, the method for testing the coulombic efficiency of electrolyte of a secondary battery under practical conditions also includes: during the coulombic efficiency test, applying a predetermined pressure to the battery cell to be tested, and performing a constant current charge and discharge test under the applied pressure.

[0013] Furthermore, the method for testing the coulombic efficiency of a secondary battery electrolyte under practical conditions also includes: when applying a predetermined pressure to a cell to be tested, applying predetermined pressures of different magnitudes to a plurality of cells to be tested, respectively, and testing the coulombic efficiency of each cell to be tested under different pressure magnitudes.

[0014] Furthermore, the method for testing the coulombic efficiency of secondary battery electrolyte under practical conditions also includes: when a predetermined pressure is applied to the battery cell to be tested, the battery cell to be tested is placed in a fixture, the fixture includes a first clamp, a second clamp and an adjusting member located between the first clamp and the second clamp; when the battery cell to be tested is located between the first clamp and the second clamp, the adjusting member drives the first clamp and the second clamp to approach each other and apply pressure to the battery cell to be tested.

[0015] Furthermore, the method for testing the coulombic efficiency of a secondary battery electrolyte under practical conditions also includes: when injecting the electrolyte, injecting different amounts of the electrolyte to be tested into a plurality of cells to be tested respectively, and testing the coulombic efficiency of each cell to be tested under different amounts of electrolyte.

[0016] By applying the technical solution of the present application, by first preparing a lithium-copper soft-pack dry battery cell, then injecting an electrolyte to form a battery cell to be tested, and then performing a coulomb efficiency test, the amount and type of electrolyte injected after the lithium-copper soft-pack dry battery cell is formed can still be adjusted according to the requirements of the coulomb efficiency test, so that the electrolyte of the battery cell to be tested used in the coulomb efficiency test can be filled according to practical conditions, thereby improving the accuracy of the coulomb efficiency test results and avoiding the test result deviation caused by excessive electrolyte during the test of traditional button batteries. Moreover, this test method of first preparing the battery cell and then filling the electrolyte before the coulomb efficiency test improves the stability of the battery cell to be tested and avoids the test data deviation caused by the traditional button battery being assembled by the test personnel and the position of the electrode cannot be fixed, thereby improving the consistency of the test data and further improving the accuracy of the coulomb efficiency test results. The testing method of the present embodiment has the advantages of being simple, reliable in data, and highly consistent, and can test the performance of electrolytes under various practical conditions, thereby conveniently and accurately testing the coulombic efficiency of the electrolyte, greatly improving the consistency of the test data, and providing a standardized approach to the electrolyte coulombic efficiency testing method, which can horizontally compare the data of different electrolytes to be tested and establish a standard electrolyte coulombic efficiency database. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] The drawings constituting part of the present application are used to provide a further understanding of the present application. The exemplary embodiments and descriptions of the present application are used to explain the present application and do not constitute an improper limitation on the present application. In the drawings:

[0018] Figure 1 A flow chart showing a method for testing the coulombic efficiency of a secondary battery electrolyte under practical conditions is shown;

[0019] Figure 2 shows a cross-sectional view of a cell to be tested;

[0020] Figure 3 The schematic diagram of the structure of the lithium copper soft pack dry cell after packaging is shown;

[0021] Figure 4 The schematic diagram of the structure of the lithium copper soft package dry battery cell after cutting the packaging film is shown.

[0022] The above drawings include the following reference numerals:

[0023] 10. Lithium-copper soft-pack dry battery cell; 11. Copper electrode plate; 12. Lithium electrode plate; 13. Diaphragm; 14. Packaging film. DETAILED DESCRIPTION

[0024] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present application will be described in detail below with reference to the accompanying drawings and in combination with the embodiments.

[0025] It should be noted that, unless otherwise specified, all technical and scientific terms used in this application have the same meanings as commonly understood by ordinary technicians in the technical field to which this application belongs.

[0026] In the present application, unless otherwise specified, the directional words used, such as "up, down, top, bottom", usually refer to the directions shown in the drawings, or to the components themselves in the vertical, perpendicular or gravity directions; similarly, for ease of understanding and description, "inside and outside" refer to the inside and outside relative to the outline of each component itself, but the above-mentioned directional words are not used to limit the present application.

[0027] It should be noted that, in the following embodiments, a plurality refers to at least two.

[0028] In order to solve the problems of poor reliability, poor result accuracy and inability to obtain the true coulombic efficiency of electrolyte under practical conditions in the prior art coulombic efficiency test, the present application provides a method for testing the coulombic efficiency of secondary battery electrolyte under practical conditions.

[0029] Embodiment 1

[0030] like Figures 1 to 4 As shown, the present application provides a method for testing the coulombic efficiency of a secondary battery electrolyte under practical conditions, including preparing a battery cell, injecting an electrolyte and testing the coulombic efficiency, wherein the battery cell is a lithium-copper soft-pack dry battery cell 10 without injecting an electrolyte; injecting the electrolyte to be tested into the lithium-copper soft-pack dry battery cell 10 to form a battery cell to be tested; and performing a charge and discharge test on the battery cell to be tested to obtain the coulombic efficiency.

[0031] In this embodiment, by first preparing a lithium-copper soft-package dry battery cell 10, then injecting an electrolyte to form a battery cell to be tested, and then performing a coulomb efficiency test, the amount and type of electrolyte injected after the lithium-copper soft-package dry battery cell 10 is formed can still be adjusted according to the requirements of the coulomb efficiency test, so that the electrolyte of the battery cell to be tested used in the coulomb efficiency test can be filled according to practical conditions, thereby improving the accuracy of the coulomb efficiency test result and avoiding the test result deviation caused by excessive electrolyte during the test of traditional button batteries. In addition, this test method of first preparing the battery cell and then filling the electrolyte before the coulomb efficiency test improves the stability of the battery cell to be tested and avoids the test data deviation caused by the traditional button battery being assembled by the test personnel and the position of the electrode cannot be fixed, thereby improving the consistency of the test data and further improving the accuracy of the coulomb efficiency test result. The testing method of the present embodiment has the advantages of being simple, reliable in data, and highly consistent, and can test the performance of electrolytes under various practical conditions, thereby conveniently and accurately testing the coulombic efficiency of the electrolyte, greatly improving the consistency of the test data, and providing a standardized approach to the electrolyte coulombic efficiency testing method, which can horizontally compare the data of different electrolytes to be tested and establish a standard electrolyte coulombic efficiency database.

[0032] In this embodiment, the method for testing the coulombic efficiency of the electrolyte of a secondary battery under practical conditions also includes: when preparing the battery cell, cutting a plurality of pole pieces of a predetermined size; stacking the negative lithium electrode pole piece 12, the separator 13 and the positive copper electrode pole piece 11 in sequence to form a lithium copper soft package dry battery cell 10; connecting the negative lithium electrode pole piece 12 and the positive copper electrode pole piece 11 to the pole ears respectively; packaging the lithium copper soft package dry battery cell 10 to prepare for the coulombic efficiency test. The packaged lithium copper soft package dry battery cell 10 is as follows Figure 3 As shown, its internal structure is as follows Figure 2 As shown, the specific preparation process of the lithium copper soft package dry battery cell 10 used in this embodiment is as follows: first, the pole pieces are prepared, and the lithium strips and copper foils are die-cut into lithium electrode pole pieces 12 and copper electrode pole pieces 11 of appropriate sizes, and then the pole pieces are stacked. The lithium electrode pole pieces 12, copper electrode pole pieces 11, and diaphragms 13 are assembled into dry battery cells in a dry environment using a stacking machine, and then the pole ears are welded. The lithium electrode pole pieces 12 are welded to nickel pole ears, and the copper electrode pole pieces 11 are welded to aluminum-to-nickel pole ears. Finally, the lithium copper soft package dry battery cell 10 is packaged with an aluminum-plastic film. In this way, the preparation of the lithium copper soft package dry battery cell 10 that has not been injected with electrolyte is completed. The lithium copper soft package dry battery cell 10 prepared in this process has a standard preparation process and size requirements, and the pole ears are reliably fixed, thereby improving the consistency of the lithium copper soft package dry battery cell 10, and further improving the consistency and accuracy of the coulomb test efficiency. It should be noted that the lithium copper soft package dry battery cell 10 is completely wrapped in an aluminum-plastic film. Figure 2 Only part of the aluminum-plastic film is shown.

[0033] In this embodiment, the method for testing the coulombic efficiency of electrolyte of a secondary battery under practical conditions further includes: when cutting the electrode pieces, the size of the lithium electrode piece 12 as the negative electrode is smaller than the size of the copper electrode piece 11 as the positive electrode.

[0034] In this embodiment, the method for testing the coulombic efficiency of the electrolyte of a secondary battery under practical conditions further includes: when the pole pieces are stacked and assembled into a dry battery cell, a separator 13 is provided between two adjacent stacked pole pieces, and the number of lithium electrode pole pieces 12 as negative electrodes is less than the number of copper electrode pole pieces 11 as positive electrodes. In this embodiment, the lithium electrode pole pieces 12 are provided as N pieces, and the copper electrode pole pieces 11 are provided as N+1 pieces, where N≥1 and N is an integer.

[0035] In the present embodiment, the method for testing the coulombic efficiency of the electrolyte of a secondary battery under practical conditions also includes: when cutting the electrode sheets, the width of the lithium electrode electrode sheet 12 as the negative electrode is 55-65cm, the length is 65-75cm, and the thickness is 30-300μm; the width of the copper electrode electrode sheet 11 as the positive electrode is 67-77cm, the length is 57-67cm, and the thickness is 10-50μm. In this way, specific sizes are specified for the lithium electrode electrode sheet 12 as the negative electrode and the copper electrode electrode sheet 11 as the positive electrode. When a plurality of lithium-copper soft-package dry cells 10 are prepared, the consistency of the lithium-copper soft-package dry cells 10 can be improved, thereby improving the consistency and accuracy of the coulombic test efficiency data. Of course, the size of the negative lithium electrode sheet 12 and the positive copper electrode sheet 11 are not limited thereto. According to actual test requirements, the negative lithium electrode sheet 12 and the positive copper electrode sheet 11 can also be set to other sizes to meet the preparation of the lithium-copper soft-pack dry battery cell 10 in this embodiment.

[0036] In this embodiment, the method for testing the coulombic efficiency of the electrolyte of a secondary battery under practical conditions further includes: when injecting the electrolyte, cutting the packaging film 14 outside the lithium copper soft package dry battery cell 10, and the cut lithium copper soft package dry battery cell 10 is as follows: Figure 4 As shown, the electrolyte to be tested is injected into the lithium copper soft package dry battery cell 10, and the cut part of the packaging film 14 is sealed. That is to say, unlike the preparation method of the traditional button battery, which first injects the electrolyte and then packages the battery, the lithium copper soft package dry battery cell 10 of this embodiment is a packaged battery cell. When the electrolyte to be tested needs to be injected, an opening is made at the packaging film 14, and after the electrolyte to be tested is injected, the opening is sealed, thereby improving the consistency of the battery cell to be tested, and avoiding the situation in which the packaging of the battery in the traditional button battery requires the operator to operate it by himself, and the operation conditions of different operators are not consistent.

[0037] In this embodiment, the method for testing the coulombic efficiency of the electrolyte of a secondary battery under practical conditions also includes: when preparing the battery cell, preparing a plurality of lithium copper soft-package dry battery cells 10; when injecting the electrolyte, injecting different electrolytes to be tested into different lithium copper soft-package dry battery cells 10; during the coulombic efficiency test, respectively, the battery cells to be tested containing different electrolytes to be tested are subjected to constant current charge and discharge tests, the coulombic efficiency of each battery cell to be tested is obtained, and the coulombic efficiency of each battery cell to be tested is compared, so that the test results of the coulombic efficiency of each battery cell to be tested can be compared when different electrolytes to be tested are filled. The amount of electrolyte injected can be determined according to the capacity of the specific lithium copper soft-package dry battery cell 10 and the test environment, and the electrolyte injection amount and the test environment of each battery cell to be tested can be ensured to be the same. Optionally, the electrolytes to be tested filled in this embodiment are electrolyte No. 1 and electrolyte No. 2, respectively. Of course, electrolyte No. 3, electrolyte No. 4, etc. can also be set according to actual test needs.

[0038] It should be noted that the electrolyte formula No. 1 of this embodiment is LiFSI+DME+TTE, LiFSI is bis(fluorosulfonyl)imide lithium salt, which has the advantages of high conductivity, high thermal stability, high electrochemical stability, hydrolysis resistance, and improved cycle life; DME is dimethyl ether; TTE is tetrafluoroethyl or tetrafluoropropyl ether; the electrolyte formula No. 2 is LiFSI+DME, so that the effect of different electrolytes on coulomb efficiency can be tested. Of course, the electrolyte to be tested can also choose other formulas to test the effect of other electrolyte formulas on coulomb efficiency.

[0039] In this embodiment, the method for testing the coulombic efficiency of the electrolyte of a secondary battery under practical conditions further includes: during the coulombic efficiency test, the test environment of each battery cell to be tested is the same, that is, the only variable between the battery cells to be tested is that the electrolyte to be tested is different, and the other conditions are exactly the same, such as the injection system, the applied pressure, the test temperature, etc. are all the same, wherein the test voltage range is -0.5V to 1V, and the test condition is 0.3mA cm -2 、1.5mAh cm -2 Charge and discharge.

[0040] In this embodiment, the method for testing the coulombic efficiency of a secondary battery electrolyte under practical conditions further includes: during the coulombic efficiency test, applying a predetermined pressure to the battery cell to be tested, and performing a constant current charge and discharge test under the applied pressure to obtain the coulombic efficiency of the battery cell to be tested.

[0041] In this embodiment, the method for testing the coulombic efficiency of the electrolyte of a secondary battery under practical conditions also includes: when a predetermined pressure is applied to the battery cell to be tested, the battery cell to be tested is placed in a fixture, the fixture includes a first clamp, a second clamp and an adjusting member located between the first clamp and the second clamp, when the battery cell to be tested is located between the first clamp and the second clamp, the adjusting member drives the first clamp and the second clamp to approach each other and applies pressure to the battery cell to be tested. Specifically, the first clamp of this embodiment is set as a rectangular plate, the second clamp is set as a rectangular plate of the same size as the first clamp, and the first clamp and the second clamp are stacked, the first clamp and the second clamp are adjusted by screws to adjust the spacing between the two, the edge of the first clamp is provided with a threaded hole, the threaded hole is at least provided at two opposite edges of the first clamp, so that the screw passing through the through hole of the second clamp is connected to the first clamp and the spacing is adjusted, the battery cell to be tested is placed between two opposite edges provided with a threaded hole, when the spacing between the first clamp and the second clamp is different, the pressure applied to the battery cell to be tested is different. Of course, the structure of the first clamp and the second clamp can be exchanged without affecting its use effect.

[0042] This embodiment also provides a method for comparing the results of the coulomb efficiency test of the battery cell to be tested and the button battery of this embodiment. Specifically, two battery cells to be tested are prepared, and electrolyte No. 1 and electrolyte No. 2 are filled respectively as test group 1 and test group 2. Two button batteries are prepared, and electrolyte No. 1 and electrolyte No. 2 are filled respectively as comparison group 1 and comparison group 2. The above two battery cells to be tested and the two button batteries are placed in the same environmental conditions and the same predetermined pressure is applied in the fixture. The charge and discharge test is continued to obtain the measurement results in Table 1. According to this measurement result, it can be seen that the coulomb test results of the battery cell to be tested in this embodiment have higher consistency and accuracy. Of course, the test group and the comparison group can also be set to 1 group, 3 groups or more groups. For example, three test groups and three comparison groups can be set at the same time, each test group is filled with three different electrolytes to be tested, each comparison group is also filled with three different electrolytes to be tested, and the formula of the three electrolytes to be tested filled in each test group is the same as the formula of the three electrolytes to be tested filled in each comparison group. The button batteries of comparison group 1 and comparison group 2 of this embodiment are both lithium copper batteries CR2025, wherein the lithium sheet has a specification of φ15.6 mm and a thickness of 450 μm, and the copper sheet has a specification of φ18 mm and a thickness of 10 μm. In this embodiment, three parallel samples are used for testing each test group and each comparison group to observe the consistency of the data of each test group and each comparison group. Of course, more samples can be set, and at least two samples are set.

[0043] Table 1 Coulomb efficiency data

[0044]

[0045] According to the results of the above tests, that is, the horizontal comparison of the data in Table 1 above, it can be seen that for the two test groups, the numerical difference between the three parallel samples of each is extremely small, while the numerical difference between the three parallel samples of the two comparison groups is relatively large, which shows that the accuracy of the conclusion obtained by the testing method of this embodiment is greatly improved.

[0046] It should be noted that, based on the principle of the controlled variable method, in the coulomb efficiency test in this embodiment, the injection coefficient, applied pressure, test temperature and other conditions of each cell to be tested are kept consistent.

[0047] Embodiment 2

[0048] The difference between this embodiment and the first embodiment is that the variables in the coulombic efficiency test are different. The only variable between the multiple cells to be tested in the first embodiment is filling with different electrolytes to be tested, while the only variable between the multiple cells to be tested in this embodiment is applying different sizes of predetermined pressures.

[0049] In this embodiment, the method for testing the coulombic efficiency of the electrolyte of a secondary battery under practical conditions also includes: when applying a predetermined pressure to the battery cell to be tested, applying predetermined pressures of different magnitudes to the multiple battery cells to be tested, testing the coulombic efficiency of each battery cell to be tested under different pressure magnitudes, thereby testing the true coulombic efficiency under practical conditions, and obtaining the best predetermined pressure. In this way, the testing process of this embodiment is to first prepare multiple battery cells to be tested, fill them with the same electrolyte, and then, when performing the coulombic efficiency test, apply predetermined pressures of different magnitudes to each battery cell to be tested, and obtain the coulombic efficiency data of each battery cell to be tested for comparison.

[0050] Embodiment 3

[0051] The difference between this embodiment and Embodiment 1 and Embodiment 2 lies in that the variables in the coulombic efficiency test are different. The only variable between the multiple cells to be tested in Embodiment 1 is filling with different electrolytes to be tested, the only variable between the multiple cells to be tested in Embodiment 2 is applying predetermined pressures of different sizes, and the only variable between the multiple cells to be tested in this embodiment is the different amount of electrolyte injected into each cell to be tested.

[0052] In this embodiment, the method for testing the coulombic efficiency of the electrolyte of a secondary battery under practical conditions also includes: when injecting the electrolyte, injecting different amounts of the electrolyte to be tested into a plurality of cells to be tested, testing the coulombic efficiency of each cell to be tested under different amounts of electrolyte, thereby obtaining the true coulombic efficiency under practical conditions and obtaining the optimal electrolyte filling amount. In this way, the testing process of this embodiment is to first prepare a plurality of cells to be tested, fill them with electrolytes of the same formula, but with different electrolyte filling amounts, and then, when performing the coulombic efficiency test, apply a predetermined pressure of the same magnitude to each cell to be tested, and other test environments are the same, and obtain the coulombic efficiency data of each cell to be tested for comparison.

[0053] It should be noted that, the multiple in the above embodiments refers to at least two.

[0054] From the above description, it can be seen that the above embodiments of the present application achieve the following technical effects:

[0055] 1. Solve the problem of poor accuracy of coulomb efficiency test results in the prior art;

[0056] 2. By first preparing a lithium copper soft package dry cell, then injecting an electrolyte to form a cell to be tested, and then performing a coulomb efficiency test, the amount and type of electrolyte injected after forming the lithium copper soft package dry cell can still be adjusted according to the requirements of the coulomb efficiency test, so that the electrolyte of the cell to be tested used in the coulomb efficiency test can be filled according to practical conditions, thereby improving the accuracy of the coulomb efficiency test result and avoiding the test result deviation caused by excessive electrolyte in the test of traditional button batteries;

[0057] 3. This test method of preparing the battery cell first and then filling the electrolyte before the coulomb efficiency test improves the stability of the battery cell to be tested, avoids the test data deviation caused by the traditional button battery being assembled by the test personnel and the position of the pole piece cannot be fixed, thereby improving the consistency of the test data and further improving the accuracy of the coulomb efficiency test results;

[0058] 4. This test method has the advantages of simplicity, reliable data, high consistency, and can test the performance of electrolytes under various practical conditions, thereby simply and accurately testing the coulombic efficiency of the electrolyte, greatly improving the consistency of the test data, and providing a standardized approach to the electrolyte coulombic efficiency test method. It can horizontally compare the data of different electrolytes to be tested and establish a standard electrolyte coulombic efficiency database.

[0059] Obviously, the embodiments described above are only part of the embodiments of this application, not all of the embodiments. Based on the embodiments in this application, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of this application.

[0060] It should be noted that the terms used herein are only for describing specific embodiments and are not intended to limit the exemplary embodiments according to the present application. As used herein, unless the context clearly indicates otherwise, the singular form is also intended to include the plural form. In addition, it should be understood that when the terms "comprise" and / or "include" are used in this specification, it indicates the presence of features, steps, operations, devices, components and / or combinations thereof.

[0061] It should be noted that the terms "first", "second", etc. in the specification and claims of the present application and the above-mentioned drawings are used to distinguish similar objects, and are not necessarily used to describe a specific order or sequence. It should be understood that the numbers used in this way can be interchanged where appropriate, so that the embodiments of the present application described herein can be implemented in an order other than those illustrated or described herein.

[0062] The above description is only the preferred embodiment of the present application and is not intended to limit the present application. For those skilled in the art, the present application may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.

Claims

1. A method for testing the coulombic efficiency of a secondary battery electrolyte under practical conditions, characterized in that: include: Prepare a battery cell, wherein the battery cell is a lithium copper soft package dry battery cell (10) that is not injected with an electrolyte; Injecting electrolyte, injecting the electrolyte to be tested into the lithium copper soft package dry battery cell (10) to form a battery cell to be tested; Coulomb efficiency test: the battery cell to be tested is subjected to charge and discharge test to obtain the coulomb efficiency.

2. The method for testing the coulombic efficiency of a secondary battery electrolyte under practical conditions according to claim 1, characterized in that: The method for testing the coulombic efficiency of the electrolyte of a secondary battery under practical conditions also includes: when preparing the battery cell, Cutting a plurality of pole pieces of predetermined sizes; A lithium electrode plate (12) as a negative electrode, a separator (13) and a copper electrode plate (11) as a positive electrode are sequentially stacked and assembled into the lithium-copper soft-pack dry battery cell (10); The lithium electrode plate (12) as the negative electrode and the copper electrode plate (11) as the positive electrode are connected to the pole lugs respectively; The lithium-copper soft-pack dry battery cell (10) is packaged.

3. The method for testing the coulombic efficiency of a secondary battery electrolyte under practical conditions according to claim 2, characterized in that: The method for testing the coulombic efficiency of the electrolyte of a secondary battery under practical conditions also includes: When the pole pieces are cut, the size of the lithium electrode pole piece (12) serving as the negative electrode is smaller than the size of the copper electrode pole piece (11) serving as the positive electrode.

4. The method for testing the coulombic efficiency of a secondary battery electrolyte under practical conditions according to claim 2, characterized in that: The method for testing the coulombic efficiency of the electrolyte of a secondary battery under practical conditions also includes: When the pole pieces are stacked and assembled into a dry battery cell, the separator (13) is provided between two adjacent stacked pole pieces, and the number of the lithium electrode pole pieces (12) serving as negative electrodes is less than the number of the copper electrode pole pieces (11) serving as positive electrodes.

5. The method for testing the coulombic efficiency of a secondary battery electrolyte under practical conditions according to claim 2, characterized in that: The method for testing the coulombic efficiency of the electrolyte of a secondary battery under practical conditions also includes: When cutting the electrode sheets, the width of the lithium electrode sheet (12) as the negative electrode is 55-65 cm, the length is 65-75 cm, and the thickness is 30-300 μm; the width of the copper electrode sheet (11) as the positive electrode is 67-77 cm, the length is 57-67 cm, and the thickness is 10-50 μm.

6. The method for testing the coulombic efficiency of a secondary battery electrolyte under practical conditions according to claim 1, characterized in that: The method for testing the coulombic efficiency of the electrolyte of a secondary battery under practical conditions also includes: When injecting the electrolyte, the packaging film (14) outside the lithium-copper soft-package dry battery cell (10) is cut, the electrolyte to be tested is injected into the lithium-copper soft-package dry battery cell (10), and the cut portion of the packaging film (14) is sealed.

7. The method for testing the coulombic efficiency of a secondary battery electrolyte under practical conditions according to claim 1, characterized in that: The method for testing the coulombic efficiency of the electrolyte of a secondary battery under practical conditions also includes: When preparing the battery cell, a plurality of the lithium copper soft pack dry battery cells (10) are prepared; When injecting the electrolyte, injecting different electrolytes to be tested into different lithium-copper soft-pack dry cells (10); During the coulombic efficiency test, constant current charge and discharge tests are performed on the cells to be tested that contain different electrolytes to be tested, the coulombic efficiency of each cell to be tested is obtained, and the coulombic efficiency of each cell to be tested is compared.

8. The method for testing the coulombic efficiency of a secondary battery electrolyte under practical conditions according to claim 7, characterized in that: The method for testing the coulombic efficiency of the electrolyte of a secondary battery under practical conditions also includes: During the coulomb efficiency test, the test environment of each of the cells to be tested is the same, wherein the test voltage range is -0.5V to 1V.

9. The method for testing the coulombic efficiency of a secondary battery electrolyte under practical conditions according to claim 1, characterized in that: The method for testing the coulombic efficiency of the electrolyte of a secondary battery under practical conditions also includes: During the coulomb efficiency test, a predetermined pressure is applied to the battery cell to be tested, and a constant current charge and discharge test is performed under the applied pressure.

10. The method for testing the coulombic efficiency of a secondary battery electrolyte under practical conditions according to claim 9, characterized in that: The method for testing the coulombic efficiency of the electrolyte of a secondary battery under practical conditions also includes: When the predetermined pressure is applied to the battery cell to be tested, predetermined pressures of different magnitudes are applied to the plurality of battery cells to be tested respectively, and the coulombic efficiency of each of the battery cells to be tested under different pressure magnitudes is tested.

11. The method for testing the coulombic efficiency of a secondary battery electrolyte under practical conditions according to claim 9, characterized in that: The method for testing the coulombic efficiency of the electrolyte of a secondary battery under practical conditions also includes: When a predetermined pressure is applied to the battery cell to be tested, the battery cell to be tested is placed in a fixture, and the fixture includes a first clamping plate, a second clamping plate, and an adjusting member located between the first clamping plate and the second clamping plate. When the battery cell to be tested is located between the first clamping plate and the second clamping plate, the adjusting member drives the first clamping plate and the second clamping plate to approach each other and applies pressure to the battery cell to be tested.

12. The method for testing the coulombic efficiency of a secondary battery electrolyte under practical conditions according to claim 1, characterized in that: The method for testing the coulombic efficiency of the electrolyte of a secondary battery under practical conditions also includes: When injecting the electrolyte, different amounts of the electrolyte to be tested are injected into the plurality of cells to be tested respectively, and the coulombic efficiency of each cell to be tested under different amounts of the electrolyte is tested.